Efficacy and Safety Evaluation of Human Growth Hormone Therapy in Patients with Idiopathic Short Stature in Korea – A Randomised Controlled Trial. Issue 1 (2020) - Jung, Min Ho; Suh, Byung-Kyu; Ko, Cheol Woo; Lee, Kee-Hyoung; Jin, Dong-Kyu; Yoo, Han-Wook; Hwang, Jin Soon; Chung, Woo Yeong; Han, Heon-Seok; Prusty, Vinay; Kim, Ho-Seong
No abstract available